Postmarketing Reevaluation of Chinese Traditional Therapy Kangbingdu Oral Liquid in the Treatment of the Common Cold. (1st September 2022) - Li, Hongjiao; Ai, Yanke; Zhao, Tianyi; Zhang, Di; Lv, Xiaoying; Jia, Shaoyan; Wen, Zehuai; Li, Guoxin; Wang, Hongyu; Gao, Feng; Li, Shaohong; Ge, Zhishan; et al.
Abstract : Background . Observational studies from China suggest that Kangbingdu oral liquid (KBD) may be effective in treating the common cold. Objective . Reevaluation of efficacy and safety of Kangbingdu oral liquid after marketing and expanding population. Design . Prospective, Pragmatic randomized controlled trial (Chictr.org.cn registration number: chiCTR-TRC-12002399). Setting . Eleven hospitals from 3 provinces in China. Patients were recruited through 11 centers, including 7 teaching hospitals, 2 University health services, one military clinic, and one community hospital. Patients . 2647 persons aged 18 to 75 years with Common cold. Intervention . Patients were randomly allocated to 2 groups: the treatment group Kangbingdu oral liquid (composed of 9 Chinese herbal medicines and honey) and the placebo group were divided into a standard-dose group of 10 ml every time, a middle dose group of 20 ml every time, high dose group of 30 ml every time, 3 times daily. Interventions and control were given for 5 days. Measurements . The primary outcome is the mean amount of total scores measured by the 11-primary symptoms: to observe the change of main symptoms from severe to disappear and to calculate and compare the mean amount of total scores after the periods of observation. Secondary outcomes are the disappearance rate of each symptom and the median time of body temperature returned to normal. Results . On day 5, the Kangbingdu liquid group had significant reductions in the mean amount of total scores measured by the 11-primary symptoms (7.39 [95% CI 7.26 to 7.51] compared to the placebo group (6.43 [95%: CI 6.24 to 6.62]). The Kangbingdu liquid can improve the remission rate of accompanying symptoms on day 5 including aversion to wind, aversion to cold, fever, cough, stuffy, runny nose, sore throat, muscular aches, headache, fatigue, and sweat (P < 0.0001 ). Significant reductions in time of body temperature to return to normal in the Kangbingdu liquid group (P50, 48.33 [95% CI 46.00 to 52.50] compared with the control group (P50, 64.59 [95% CI 51.08 to 70.50] (P = 0.0022 ). 13 (0.7%) participants in the Kangbingdu liquid group and 1(0.2%) participants in the placebo group (P > 0.05 ) had treatment-related AEs, which mainly include diarrhea and dyspepsia in the Kangbingdu liquid group and constipation in the placebo group. Conclusion . The study's conclusion in this paper was based on the placebo, Kangbingdu oral liquid two groups which clinically diagnosed the common cold and flu. (1) Kangbingdu oral liquid can effectively improve the comprehensive clinical symptoms of common adult cold, also improved main symptoms, including sore throat, muscle aches, headache, and so on. (2) Kangbingdu oral liquid effectively shortens the time of body temperature to return to normal.